7T MRI Visualization of Cortical Lesions in Adolescents and Young Adults with Pediatric‐Onset Multiple Sclerosis. Issue 5 (10th August 2017) - Datta, Ritobrato; Sethi, Varun; Ly, Sophia; Waldman, Amy T.; Narula, Sona; Dewey, Blake E.; Sati, Pascal; Reich, Daniel; Banwell, Brenda
ABSTRACT: BACKGROUND: Cortical pathology in multiple sclerosis (MS) has been associated with prolonged and progressive disease. 7T magnetic resonance imaging (MRI) provides enhanced visualization of cortical lesions (CLs). Hence, we conducted a pilot study to explore whether CLs occur early in MS, as evidenced by pediatric‐onset patients. METHODS: A total of 8 pediatric‐onset MS patients were imaged using 7T MRI. CLs were annotated on T1‐weighted magnetization‐prepared rapid acquisition of gradient echoes images as leukocortical (LC), intracortical, or subpial. Total CLs, age at onset, age at scan, disease duration, total relapses, and Expanded Disability Status Scale (EDSS) score were recorded. RESULTS: A median of 120 (range: 48‐144) CLs was identified in 8 MS patients (3 female, all with relapsing remitting MS, mean age at scan 21 years ± 3.5 SD, mean age of disease onset 15 years ± 2.3 SD, mean disease duration 5.3 years ± 3.4 SD, median EDSS 2.0). Nearly all the lesions identified were LC. CONCLUSIONS: Many CLs are detectable using 7T MRI in patients with pediatric‐onset MS despite relatively brief disease duration, absence of progressive disease, and very limited physical disability—supporting early cortical involvement in MS.